Editor's Choice – Validation of the Management of Aortic Graft Infection Collaboration (MAGIC) Criteria for the Diagnosis of Vascular Graft/Endograft Infection: Results from the Prospective Vascular Graft Cohort Study. (August 2021) - Anagnostopoulos, Alexia; Mayer, Fabienne; Ledergerber, Bruno; Bergadà-Pijuan, Judith; Husmann, Lars; Mestres, Carlos A.; Rancic, Zoran; Hasse, Barbara; ,
Abstract : Objective: The timely management of vascular graft/endograft infection (VGEI) is crucial to a favourable outcome, yet can be challenging as there is no validated gold standard diagnostic test. Recently, a new case definition has been proposed by the Management of Aortic Graft Infection Collaboration (MAGIC) to close the diagnostic gap. The aim of this study was to validate the MAGIC criteria as a suggested diagnostic standard for the diagnosis of suspected VGEI in the prospective Vascular Graft Cohort study (VASGRA). Methods: VASGRA is an open, prospective, observational cohort study. Prospective participants in VASGRA between 2013 and 2019 were included (257 patients; 137 with VGEI). The accuracy of the MAGIC criteria for a diagnosis of VGEI was evaluated retrospectively by calculating the sensitivity and specificity vs. the consensually adjudicated VASGRA infection status. Results: The VASGRA cohort categorised 137 (53.3%) patients as "diseased" and 120 patients as "not diseased"; using the MAGIC criteria, 183/257 (71.2%) patients were considered to be "diseased". Thus, for the MAGIC criteria, a sensitivity of 99% (95% confidence interval [CI] 96–100) and a specificity of 61% (95% CI 52–70) were calculated. Considering suspected VGEI according to the MAGIC criteria as "not diseased" achieved congruent assessments of the VASGRA team and the MAGIC criteria, with a sensitivity of 93% and a specificity of 93%. The accuracy of the MAGIC criteria for the different graft locations were also compared. If the suspected VGEIs were assigned to the "not diseased" group, VGEIs of the thoracic aorta seemed to have a poorer sensitivity (86%; 95% CI 73–95) than the other graft locations. Conclusion: The current MAGIC criteria offer good sensitivity and specificity in the context of true infections but a reduced specificity for a possible VGEI.